Public Participation in the Establishment of Regional Regulation in Humbang Hasundutan Regency - Alfedbond Naibaho; Kasman Siburian (International Journal of Social Sciences Review, 2022)
This study discusses the participation of the community in Humbang Hasundutan Regency in the formation of regional regulations that have been regulated in the Law of the Republic of Indonesia No. 12 of 2011 concerning the Establishment of Laws and Regulations. The formation of regional regulations starts from the planning, preparation, discussion, promulgation, and dissemination stages. This research uses a conceptual framework regarding regional regulations as well as public participation in the process of forming regional regulations. This research uses a normative legal approach. The result of this study is that public participation is needed in the process of forming regional regulations because the community is the goal of the development itself so that active public participation can answer the needs of the community in the area.